Long-term disease-free survivor of metastatic large-cell neuroendocrine carcinoma of the lung treated with amrubicin and irinotecan - Shinichiro Ryuge; Shi-Xu Jiang; Mayuko Wada; Ken Katono; et al (Dove Medical Press, 2009)
Shinichiro Ryuge1, Shi-Xu Jiang2, Mayuko Wada1, Ken Katono1, Maiko Iwasaki1, Akira Takakura1, Sakiko Otani1, Yuka Kimura1, Tomoya Fukui1, Masanori Yokoba1, Masaru Kubota1, Masato Katagiri1, Kazusige Hayakawa3, Noriyuki Masuda11Department of Respiratory Medicine, 2Department of Pathology, 3Department of Radiology, Kitasato University School of Medicine, Sagamihara, Kanagawa, JapanAbstract: Large-cell neuroendocrine carcinoma (LCNEC) is a relatively uncommon variant of non-small cell lung cancer. Since the biological characteristics of LCNEC are similar to those of small cell lung cancer, LCNEC is usually treated with chemotherapy regimens used for small cell lung cancer. However, the outcomes are usually dismal. Here, we report a patient with LCNEC (a metastasis to the brain). After whole brain irradiation, he received a combination of amrubicin and irinotecan chemotherapy, and has been relapse-free for two years. This treatment regimen may be beneficial for patients with advanced LCNEC. Keywords: large-cell neuroendocrine carcinoma, chemotherapy, amrubicin, irinotecan, lung cancer